Versus [videorecording (DVD)] - Kitamura, Ryuhei; Sirabella, John; Sakaguchi, Tak; Sakai, Hideo; Misaka, Chieko; Matsuda, Kenji, 1971- (Tokyo Shock, 2003)
"Deep within the mysterious Forest of Resurrection, the spectacular battle between good and evil has gone on since the dawn of time. When Prisoner KSC2-303 escapes from a maximum security jail, he enters the forest believing it will lead him to a safe haven. Instead, he finds himself a pawn in an endless struggle played out against an ever-changing background across multiple temporal planes of existence. His opponent: a mysterious man who seemingly cannot be killed. The battle to be waged between these warriors: Good versus Evil in the pursuit of a beautiful woman who holds the power to grant eternal life. But what Prisoner KSC2-303 cannot remember is whether he is the personification of good or the very essence of darkness"--Container